A short bout of high-intensity intermittent exercise before moderate-intensity prolonged exercise as a mean to potentiate fat oxidation ?. Issue 9 (2nd May 2020) - Borowik, Anna; Chacaroun, Samarmar; Tessier, Damien; Doutreleau, Stéphane; Verges, Samuel; Flore, Patrice
ABSTRACT: Moderate-intensity continuous exercise (MICE) improves fat oxidation. High-intensity intermittent exercise (HIIE) is thought to have a greater potential for fat oxidation but it might be too demanding in the long term for patients. We hypothesized that an initial bout of HIIE could maximize fat oxidation during MICE and the following passive recovery. Eighteen healthy participants performed two acute isocaloric exercise sessions at random. MICE consisted of 45-min cycling at 50% of maximal aerobic power (Pmax). COMB began with five 1-min bouts of HIIE at Pmax (interspaced with 1-min recovery periods) followed by 35-min MICE. Gas exchange allowed substrate oxidation rate assessment. Expressed as a % of energy expenditure, fat oxidation (%) increased during in the passive recovery following COMB (Recovery: 36.0 ± 19.4 vs 23.0 ± 20.3%; ES: 0.66; p < 0.0001). An initial bout of HIIE preceding a prolonged moderate-intensity exercise may potentiate fat oxidation during the following recovery. This might be relevant for health management of overweight/obese persons.